Perswazyjnie o warsztacie dziennikarskim (na przykładzie publikacji w rubryce „Media – warsztat” miesięcznika „Press”) - Worsowicz, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article is dedicated to aspects of a journalist’s work published between 1996–2014 inthe professional monthly magazine Press, aimed at people interested in media, advertisement andpublic relations. These statements help other media professionals become familiar with the workexperience of their colleagues, as well as help acquaint new entrants to the profession with the rules,difficulties and dilemmas associated with this work. The author classifies and defines three typesof published texts: those written in an instructional form, those which approach the conventionsof an informative article, and finally, copyright protected publications. An analysis of these textsleads to a conclusion that the primary aims of the publication have led its authors to focus attention on perceptions and the practical dimensions of the knowledge being shared. They use detailed descriptions,and have gradually abandoned ready solutions, encouraging readers instead to considera range of possibilities; they also illustrate their suggestions with examples from personal experience.They do not fail to provide enlightening recollections of their own mistakes or detail the difficultbeginnings of their own careers. The role models presented demand from the reader an abilityto synthesize various elements. The original structure of the publication as well as its thoughtful andrecollection-driven approach to the subject helps to achieve this. An awareness of the technical natureof texts urges experienced journalists to explain in plain terms the ins and outs of the professionby presenting specific events, making comparisons, and offering brief advice or warnings. This alsorelates to the language of expression they use, which makes even the official and hackneyed style ofinstructional discourse easy to understand.